2018
DOI: 10.1111/nmo.13360
|View full text |Cite
|
Sign up to set email alerts
|

Galaninergic intramural nerve and tissue reaction to antral ulcerations

Abstract: The results obtained unveiled the participation of galanin and galanin receptors in the stomach tissue response to antral ulcerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
(129 reference statements)
1
10
0
Order By: Relevance
“…Further, numerous reports confirm the involvement of GAL in the control of inflammatory processes in the digestive tract [29,64]. An increase in the population of GAL-LI neurons was observed in structures of the ENS, as well as extrinsic sources of innervation of the GI tract, following colitis, gastric ulcers, hyperacidity of the stomach, and enteric Salmonella infection [24,[64][65][66]. Moreover, GAL triggers an immunological system response and modulates the synthesis of pro-inflammatory mediators, including TNF-α, IL-1α, and IL-8 [67].…”
Section: Discussionmentioning
confidence: 79%
“…Further, numerous reports confirm the involvement of GAL in the control of inflammatory processes in the digestive tract [29,64]. An increase in the population of GAL-LI neurons was observed in structures of the ENS, as well as extrinsic sources of innervation of the GI tract, following colitis, gastric ulcers, hyperacidity of the stomach, and enteric Salmonella infection [24,[64][65][66]. Moreover, GAL triggers an immunological system response and modulates the synthesis of pro-inflammatory mediators, including TNF-α, IL-1α, and IL-8 [67].…”
Section: Discussionmentioning
confidence: 79%
“…Studies have demonstrated that galanin is widely distributed throughout the gastrointestinal tract [2][3][4][5][6] and it is present both in the wall of gastrointestinal tract and the extrinsic nerves supplying the tract [7][8][9][10]. At the functional level, galanin plays a role in several biological processes in the digestive system [11][12][13][14] and, as demonstrated by the authors' previous studies, it modulates enteric nerve response to gastric ulcerations [15,16].…”
Section: Introductionmentioning
confidence: 87%
“…20 kg, obtained from a commercial fattening farm, 14-260 Lubawa, Poland), focused on the intramural stomach neuron reaction to gastric ulcerations. The detailed descriptions of all experimental procedures are enclosed in these publications [15,16,49].…”
Section: Animals Used In the Study And Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In several animal models of inflammation, expression of GAL 1 ‐R is elevated in peripheral tissue . In a porcine model of antral ulceration, elevation of GAL 1,2,3 ‐R was observed in stomach tissue, accompanied by acute inflammation . In a transgenic mouse model of experimental autoimmune encephalomyelitis, overexpression of galanin led to abolishment of the disease, whereas a loss‐of‐function mutation in the galanin gene increased disease severity .…”
Section: Introductionmentioning
confidence: 99%